2021
DOI: 10.1016/j.jhep.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-sequencing atlas reveals an MDK-dependent immunosuppressive environment in ErbB pathway-mutated gallbladder cancer

Abstract: Single-cell RNA-sequencing atlas reveals an MDK-dependent immunosuppressive environment in ErbB pathway-mutated gallbladder cancer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…Based on our results, MDK , which was secreted by GBM cancer cells, induced the migration and immunosuppressive polarization of macrophages. Our results were consistent with the role of MDK identified by Zhang et al in 2021 ( 41 ). In their gallbladder cancer research, MDK interacts with its receptor LRP1 , which is expressed by tumor-infiltrating macrophages, and further promotes immunosuppressive macrophage differentiation.…”
Section: Discussionsupporting
confidence: 94%
“…Based on our results, MDK , which was secreted by GBM cancer cells, induced the migration and immunosuppressive polarization of macrophages. Our results were consistent with the role of MDK identified by Zhang et al in 2021 ( 41 ). In their gallbladder cancer research, MDK interacts with its receptor LRP1 , which is expressed by tumor-infiltrating macrophages, and further promotes immunosuppressive macrophage differentiation.…”
Section: Discussionsupporting
confidence: 94%
“…The variability of tumor disease results from the initial genetic state of the tumor cells, their subsequent mutations, epithelialmesenchymal transition, and interactions with the innate immune system Longo (2011). Recently, in case of cancer the crosstalk of tumor cells with immune cells has been investigated in more detail Zhang et al (2021). In sepsis, the innate immune system is activated by infection and the clinical course is determined by the individual patient's initial condition.…”
Section: Introductionmentioning
confidence: 99%
“…It was also identified to contribute to multidrug resistance in GC cells 81 . Besides, MDK rewires immunosuppressive environment in melanoma and gallbladder cancer 82 83 . In this study, we found that MDK is overexpressed in EGC and AG patients comparing with NAG ones.…”
Section: Resultsmentioning
confidence: 99%